Learning a Language, Understanding a Culture: The Importance of Appropriate Social Behavior and Intercultural Competence in French as a Foreign Language (FFL) - Macías Alvarenga, Ivannia (2025)
The integration of intercultural competence into French as a Foreign Language (FFL) learning aims to promote mutual understanding and the acceptance of linguistic and cultural differences. It enables students to acquire essential cultural reference points for effective interaction with Francophone speakers. By incorporating sociocultural competence into their learning journey, students are guided to analyze cultural representations and deconstruct stereotypes. This approach encourages them to cultivate an open and respectful attitude while enhancing their adaptability and communication skills. This actively contributes to a dynamic of exchange and understanding in a multilingual and intercultural environment. Consequently, acquiring intercultural competence is essential for fostering tolerance and solidarity among cultures. Through this intercultural dimension, FLE students gain insight into the culture of the Other, develop greater empathy, and improve their understanding of other behaviors. Furthermore, this component allows them to make valuable comparisons, thereby enhancing their understanding of the differences and similarities between cultures, while also providing them the chance to share certain aspects of their own. This intercultural interaction is vital for fostering connections, forming friendships, and actively engaging in cultural exchange. In essence, incorporating intercultural competence into FLE learning serves as a means of developing social skills, enhancing understanding of others, and fostering more harmonious communication between cultures.